Fullerenol inhibits tendinopathy by alleviating inflammation - Jiao, Xin; Wang, Zengguang; Li, Yiming; Wang, Tianchang; Xu, Chen; Zhou, Xianhao; Gan, Yaokai (Frontiers in Bioengineering and Biotechnology, 2023)
Tendinopathy is a common disease in orthopaedics, seriously affecting tendon functions. However, the effects of nonsurgical treatment on tendinopathy are not satisfactory and surgical treatments possibly impair the function of tendons. Biomaterial fullerenol has been proved to show good anti-inflammatory effects on various inflammatory diseases. For in vitro experiments, primary rat tendon cells (TCs) were treated by interleukin-1 beta (IL-1β) combined with aqueous fullerenol (5, 1, 0.3μg/ml). Then inflammatory factors, tendon-related markers, migration and signaling pathways were detected. For in vivo experiments, rat tendinopathy model was constructed by local injection of collagenase into Achilles tendons of rats and fullerenol (0.5, 1mg/ml) was locally injected 7 days after collagenase injection. Inflammatory factors and tendon-related markers were also investigated. Fullerenol with good water-solubility showed excellent biocompatibility with TCs. Fullerenol could increase expression of tendon-Frelated factors (Collagen I and tenascin C) and decrease expression of inflammatory factors (matrix metalloproteinases-3, MMP-3 and MMP-13) and reactive oxygen species (ROS) level. Simultaneously, fullerenol slowed the migration of TCs and inhibited activation of Mitogen-activated protein kinase (MAPK) signaling pathway. Fullerenol also attenuated tendinopathy in vivo, including reduction of fiber disorders, decrease of inflammatory factors and increase of tendon markers. In summary, fullerenol is a promising biomaterial that can be used to treat tendinopathy.